In situ synchrotron X-ray diffraction analysis of deformation behaviour in Ti-Ni-based thin films - Wang, Hong (Journal of synchrotron radiation, 2015)
Deformation mechanisms of as-deposited and post-annealed Ti50.2Ni49.6, Ti50.3Ni46.2Cu3.5 and Ti48.5Ni40.8Cu7.5 thin films were investigated using the in situ synchrotron X-ray diffraction technique. Results showed that initial crystalline phases determined the deformation mechanisms of all the films during tensile loading. For the films dominated by monoclinic martensites (B19'), tensile stress induced the detwinning of 〈011〉 type-II twins and resulted in the preferred orientations of (002)B19' parallel to the loading direction (∥ LD) and (020)B19' perpendicular to the LD (⊥ LD). For the films dominated by austenite (B2), the austenite directly transformed into martensitic variants (B19') with preferred orientations of (002)B19' ∥ LD and (020)B19' ⊥ LD. For the Ti50.3Ni46.2Cu3.5 and Ti48.1Ni40.8Cu7.5 films, martensitic transformation temperatures decreased apparently after post-annealing because of the large thermal stress generated in the films due to the large differences in thermal expansion coefficients between the film and substrate